Calpain and JNK pathways participate in isoflurane – induced nucleus translocation of apoptosis-inducing factor in the brain of neonatal rats. (15th March 2018) - Han, Xue; Liu, Chuiliang; Zhang, Kun; Guo, Mingyan; Shen, Zhiwen; Liu, Yafang; Zuo, Zhiyi; Cao, Minghui; Li, Yujuan
Highlights: Isoflurane induced neuroapoptosis by promoting AIF translocation to nuclei. Calpain activation was necessary to isoflurane-induced AIF nuclear translocation. JNK pathway was involved in isoflurane–induced activation of m-calpain. JNK activation participated in caspase-dependent and independent neuroapoptosis. Abstract: Recent studies have demonstrated that volatile anesthetic causes caspase-dependent neuroapoptosis and persistent cognitive deficits in young animals. Apoptosis-inducing factor (AIF) can trigger apoptosis by caspase-independent pathway. Whether isoflurane induces neuroapoptosis by activation of AIF and its possible mechanism are underdetermined. Rats at postnatal day 7 were exposed to 1.1% isoflurane for 4 h and the expression of AIF, cytochrome c, caspase-3, μ-calpain, m-calpain, Bcl-2 and Bax in the mitochondrial, cytosolic, and nuclear fraction, as well as the number of both AIF and TUNEL positive neurons in the cortices of rats were measured. Moreover, the effects of calpain inhibitor MDL-28170 or JNK inhibitor SP600125 on isoflurane-induced AIF release, caspase activation and cognitive deficits were assessed. We found isoflurane activated CytC-caspase-3 dependent apoptosis pathway mainly in the early phase (0–6 h after exposure). Moreover, isoflurane activated mitochondrial μ-calpain, induced AIF truncation during early phase and activated m-calpain, induced AIF release from the mitochondria to cytosol and translocation into the nucleus in the late phase (6–24 h after exposure). MDL-28170 attenuated the isoflurane–induced mitochondrial AIF truncation, release and nuclear translocation, but did not change the expression of cleaved-caspase-3 and mitochondrial Bax and Bcl-2 proteins. SP600125 attenuated isoflurane-induced neuroapoptosis by inhibiting both AIF and caspase-3 pathways and reduced cognitive impairment in neonatal rats. This is the first study to provide the evidence that isoflurane induced AIF-dependent neuroapoptosis by activation of mitochondrial μ-calpain and m-calpain in neonatal rats. JNK inhibition reversed isoflurane-induced neuroapoptosis and subsequent long-term neurocognitive impairment, acting via inhibiting activation of both AIF and caspase-3 pathways.